2006
DOI: 10.1110/ps.062271506
|View full text |Cite
|
Sign up to set email alerts
|

The CXXC motif at the N terminus of an α‐helical peptide

Abstract: An active site containing aC XXC motif is always foundi nt he thiol-disulphide oxidoreductase superfamily. As urvey of crystals tructuresr evealed that the CXXC motif had av eryh ighl ocal propensity (26.3 6 6.2) for theNtermini of a -helices. Ahelical peptide with the sequence CAAC at the Nt erminus was synthesized to examine the helix-stabilizing capacity of the CXXC motif. Circular dichroism was used to confirm the helicalnature of thepeptide andstudy behavior under titration with various species. With DTT,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 28 publications
5
40
0
Order By: Relevance
“…Given that the two cysteines are adjacent to the TM helix (Fig. 1b) and in view of a recent study showing that a CxxC motif is found at the N termini of ␣ helices stabilizing ␣ helical structures, this juxtaposition is noteworthy (37). Assuming an intrachain disulfide is formed in each stalk region, one possibility is that the CD3␥ TM helix is stabilized and perhaps even extended as an elongated helix above the plane of the cell membrane.…”
Section: Discussionmentioning
confidence: 86%
“…Given that the two cysteines are adjacent to the TM helix (Fig. 1b) and in view of a recent study showing that a CxxC motif is found at the N termini of ␣ helices stabilizing ␣ helical structures, this juxtaposition is noteworthy (37). Assuming an intrachain disulfide is formed in each stalk region, one possibility is that the CD3␥ TM helix is stabilized and perhaps even extended as an elongated helix above the plane of the cell membrane.…”
Section: Discussionmentioning
confidence: 86%
“…Others have suggested the helix dipole (Hol et al 1978;Hol 1985;Iqbalsyah et al 2006), interaction with histidine (Polgar 1974;Lo Bello et al 1993), or ion pair formation (Griffiths et al 2002) as important features in cysteine reactivity. Integration of profiling with electrostatic analysis across the entire modifiable protein set allows us to comment generally on these observations and to identify possible mechanistic determinants for cysteine deprotonation.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, these two catalytic cysteines are presumably located near the adenylated form of U8. Second, Cys 265 and Cys 268 are at the N terminus of an ␣-helix, which is a conserved location of a CXXC motif in the thiol:disulfide oxidoreductase superfamily (60). In this superfamily, the CXXC motif is essential for the catalysis of redox reactions involving formation of reversible intramolecular disulfide bonds.…”
Section: Proposed Model Of S 4 U Formation In M Maripaludis-mentioning
confidence: 99%